The Management of Burial Land by the Tunggul Hitam Cemetery Unit (UPTD TPU) of Padang City in Addressing Burial Land Scarcity - Nafia, Zenid Imam; Helmi, Rahmadhona Fitri (The Future of Education Journal, 2025)
The limited availability of burial land in urban areas has become a significant issue in the management of public space. This study aims to analyze the management of burial land by the Tunggul Hitam Cemetery Unit (UPTD TPU) of Padang City in addressing the land scarcity issue using a public management approach. The research method used is descriptive qualitative, with data collection techniques including interviews, observations, and documentation. Data analysis was carried out interactively through processes of reduction, presentation, as well as conclusion drawing and verification. The results show that the UPTD TPU Tunggul Hitam has effectively applied the four functions of management according to George R. Terry planning, organizing, directing, and controlling despite facing various limitations. In the planning phase, the policy of land-sharing and the expansion plan for the Air Dingin cemetery are the primary strategies to address the land crisis. In organizing, task divisions are clear, but limitations in human resources and inter-departmental coordination remain obstacles. In directing, participatory leadership styles and open communication have boosted employee morale, while in controlling, field monitoring and administration are regularly carried out, although they are still limited in digital capacity. Overall, the UPTD has demonstrated an adaptive management pattern that aligns with the principles of efficiency, accountability, and sustainable public service. The findings of this study are expected to provide input for local governments in formulating integrated burial land management policies in the future.